2010
DOI: 10.1017/s0305000910000127
|View full text |Cite
|
Sign up to set email alerts
|

Early verb learning in 20-month-old Japanese-speaking children

Abstract: The present study investigated whether children's representations of morphosyntactic information are abstract enough to guide early verb learning. Using an infant-controlled habituation paradigm with a switch design, Japanese-speaking children aged 1 ; 8 were habituated to two different events in which an object was engaging in an action. Each event was paired with a novel word embedded in a single intransitive verb sentence frame. The results indicated that only 40% of the children were able to map a novel ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Children can also attach a label to the appropriate referent by monitoring the adult’s intention and gaze direction, even if the child cannot immediately see the labeled item (Baldwin, 1993a, 1993b), or if the adult finds the referent after the child has heard the label (Tomasello & Barton, 1994; Tomasello, Strosberg, & Akhtar, 1996). These findings together with the present finding of no clear object or motion bias in the absence of morphosyntactic and pragmatic cues suggest that 18‐ to 20‐month‐old infants are sensitive to the presence and absence of morphosyntactic cues and that they are ready to use morphosyntactic and pragmatic cues in word learning when these cues are simple and salient and do not consume much of their cognitive resources (Oshima‐Takane et al, in press; Shimpi & Huttenlocher, 2007).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Children can also attach a label to the appropriate referent by monitoring the adult’s intention and gaze direction, even if the child cannot immediately see the labeled item (Baldwin, 1993a, 1993b), or if the adult finds the referent after the child has heard the label (Tomasello & Barton, 1994; Tomasello, Strosberg, & Akhtar, 1996). These findings together with the present finding of no clear object or motion bias in the absence of morphosyntactic and pragmatic cues suggest that 18‐ to 20‐month‐old infants are sensitive to the presence and absence of morphosyntactic cues and that they are ready to use morphosyntactic and pragmatic cues in word learning when these cues are simple and salient and do not consume much of their cognitive resources (Oshima‐Takane et al, in press; Shimpi & Huttenlocher, 2007).…”
Section: Discussionsupporting
confidence: 73%
“…The present experiment has recently been replicated by providing Japanese‐speaking 20‐month‐old infants with verb morphosyntactic cues to the bare word. The results showed that 20‐month‐olds mapped novel words onto the motion and not onto the agent (Oshima‐Takane, Ariyama, Kobayashi, Katerelos & Poulin‐Dubois, in press). Furthermore, there is evidence to suggest that children’s emerging ability to attend to socio‐pragmatic information may be particularly important in allowing them to detect and label motions in a linguistic context.…”
Section: Discussionmentioning
confidence: 99%
“…English‐learning toddlers used neighboring functors to interpret a novel word as referring to transitive versus intransitive actions (e.g., Naigles, ; Yuan & Fisher, ). Morphosyntactic cues involving functors (e.g., a _; is _‐ ing ) also support toddlers' learning of the meanings of nouns and verbs (i.e., object vs. action) in other languages (e.g., French: Bernal, Lidz, Millote, & Christophe, ; Japanese: Oshima‐Takane, Ariyama, Kobayashi, Katerelos, & Poulin‐Dubois, ). Infants understand that functors are more structural than semantic; 17‐month‐olds were familiarized with a foreign language, and then they heard a functor and a lexical word from that language while viewing a novel object (Hochmann, Endress, & Mehler, ).…”
Section: Functional Morphemes Bootstrap Language Acquisitionmentioning
confidence: 96%
“…To determine whether infants’ attention to objects and actions was guided by language, another study focused specifically on the influence of introducing novel verbs (Oshima‐Takane, Ariyama, Kobayashi, Katerelos, & Poulin‐Dubois, ). Japanese 20‐month‐olds were tested in the same paradigm described above, but this time, the novel word was embedded in a phrase that marked it as a verb (e.g., “It's blicking!”).…”
Section: New Cross‐linguistic Evidence From Infantsmentioning
confidence: 99%